Evaluation of de novo donor specific antibodies after kidney transplantation in the era of donor-derived cell-free DNA - Tian, Yuan; Frischknecht, Lukas; Mallone, Anna; Rössler, Fabian; Schachtner, Thomas; Nilsson, Jakob (Frontiers in Immunology, 2025)
BackgroundDonor-derived cell-free DNA (dd-cfDNA) is a promising non-invasive biomarker for detecting graft injury in solid organ transplant recipients. Elevated dd-cfDNA levels are strongly associated with rejection and graft injury, especially antibody-mediated rejection (ABMR). While de novo donor-specific antibodies (dnDSA) are crucial in ABMR, the relationship between dd-cfDNA levels and dnDSA features, such as DSA category, MFI and HLA target loci, remains unclear.MethodsWe analyzed dd-cfDNA levels in 75 kidney transplant recipients who developed dnDSA post-transplant. dnDSA were categorized as “true”, “possible”, or “false” based on bead reactivity patterns and HLA typing. dd-cfDNA was assessed alongside dnDSA detection and sequential follow-up samples in a subgroup.Results“True” dnDSA showed significantly higher dd-cfDNA levels compared to “possible” and “false” groups. None of the dd-cfDNA values in the “false” group exceeded 0.6%, and only a small fraction of the “possible” group had values slightly above 0.6%. dd-cfDNA levels were not significantly affected by dnDSA target loci or number. A strong correlation between cumulative dnDSA MFI and dd-cfDNA levels was observed, especially in patients with “true” HLA-DQ-directed dnDSA. Sequential dd-cfDNA analysis showed dynamic changes in 25% of patients, all from the “true” dnDSA group, which tended to align with shifts in cumulative MFI over time.ConclusionThese findings highlight the correlation between cumulative dnDSA MFI and dd-cfDNA levels, particularly in HLA-DQ-directed dnDSA, and suggest graft injury is dynamic in dnDSA-positive patients. Integrated monitoring of dnDSA and dd-cfDNA offers a promising non-invasive approach for assessing graft injury and alloimmunity, potentially enhancing post-transplant care.